The Multitasking Reality of the Parenting Brain. (3rd April 2019) - Ablow, Jennifer C.; Measelle, Jeffrey R.
SYNOPSIS: Ecologically valid experimental paradigms are critical if we are to identify meaningful behavioral and neural substrates of parental responsiveness to infant cues. In this commentary, we discuss how Rigo et al. (2019) in their fMRI study of responses to infant cues make advances toward developing a paradigm that better mimics real-world parenting demands. In contrast to the standard infant cue paradigm, Rigo and colleagues exposed participants to infant sounds while engaged in competing goal-directed demands – multitasking. Although several central hypotheses were not confirmed, we hold that the use of ecologically improved paradigms is a necessary step toward understanding the multitasking reality of the parenting brain.